Motor learning changes the axon initial segment of the spinal motoneuron. - Wang, Yu; Chen, Yi; Chen, Lu; Herron, Bruce J; Chen, Xiang Yang; Wolpaw, Jonathan R (J Physiol, 2024)
We are studying the mechanisms of H-reflex operant conditioning, a simple form of learning. Modelling studies in the literature and our previous data suggested that changes in the axon initial segment (AIS) might contribute. To explore this, we used blinded quantitative histological and immunohistochemical methods to study in adult rats the impact of H-reflex conditioning on the AIS of the spinal motoneuron that produces the reflex. Successful, but not unsuccessful, H-reflex up-conditioning was associated with greater AIS length and distance from soma; greater length correlated with greater H-reflex increase. Modelling studies in the literature suggest that these increases may increase motoneuron excitability, supporting the hypothesis that they may contribute to H-reflex increase. Up-conditioning did not affect AIS ankyrin G (AnkG) immunoreactivity (IR), p-p38 protein kinase IR, or GABAergic terminals. Successful, but not unsuccessful, H-reflex down-conditioning was associated with more GABAergic terminals on the AIS, weaker AnkG-IR, and stronger p-p38-IR. More GABAergic terminals and weaker AnkG-IR correlated with greater H-reflex decrease. These changes might potentially contribute to the positive shift in motoneuron firing threshold underlying H-reflex decrease; they are consistent with modelling suggesting that sodium channel change may be responsible. H-reflex down-conditioning did not affect AIS dimensions. This evidence that AIS plasticity is associated with and might contribute to H-reflex conditioning adds to evidence that motor learning involves both spinal and brain plasticity, and both neuronal and synaptic plasticity. AIS properties of spinal motoneurons are likely to reflect the combined influence of all the motor skills that share these motoneurons. KEY POINTS: Neuronal action potentials normally begin in the axon initial segment (AIS). AIS plasticity affects neuronal excitability in development and disease. Whether it does so in learning is unknown. Operant conditioning of a spinal reflex, a simple learning model, changes the rat spinal motoneuron AIS. Successful, but not unsuccessful, H-reflex up-conditioning is associated with greater AIS length and distance from soma. Successful, but not unsuccessful, down-conditioning is associated with more AIS GABAergic terminals, less ankyrin G, and more p-p38 protein kinase. The associations between AIS plasticity and successful H-reflex conditioning are consistent with those between AIS plasticity and functional changes in development and disease, and with those predicted by modelling studies in the literature. Motor learning changes neurons and synapses in spinal cord and brain. Because spinal motoneurons are the final common pathway for behaviour, their AIS properties probably reflect the combined impact of all the behaviours that use these motoneurons.
Keywords: Animals; Ankyrins; Axon Initial Segment; Axons; Conditioning, Operant; H-Reflex; Learning; Male; Motor Neurons; Neuronal Plasticity; Rats; Rats, Sprague-Dawley; Spinal Cord

Why New Spinal Cord Plasticity Does Not Disrupt Old Motor Behaviors - Chen, Yi; Chen, Lu; Wang, Yu; Chen, Xiang Yang; Jonathan Wolpaw (The Journal of Neuroscience, 2017)
When new motor learning changes the spinal cord, old behaviors are not impaired; their key features are preserved by additional compensatory plasticity. To explore the mechanisms responsible for this compensatory plasticity, we transected the spinal dorsal ascending tract before or after female rats acquired a new behavior—operantly conditioned increase or decrease in the right soleus H-reflex—and examined an old behavior—locomotion. Neither spinal dorsal ascending tract transection nor H-reflex conditioning alone impaired locomotion. Nevertheless, when spinal dorsal ascending tract transection and H-reflex conditioning were combined, the rats developed a limp and a tilted posture that correlated in direction and magnitude with the H-reflex change. When the right H-reflex was increased by conditioning, the right step lasted longer than the left and the right hip was higher than the left; when the right H-reflex was decreased by conditioning, the opposite occurred. These results indicate that ascending sensory input guides the compensatory plasticity that normally prevents the plasticity underlying H-reflex change from impairing locomotion. They support the concept of the state of the spinal cord as a negotiated equilibrium that reflects the concurrent influences of all the behaviors in an individual's repertoire; and they support the new therapeutic strategies this concept introduces.
Keywords: H-Reflex; motor learning; operant conditioning; plasticity; Rehabilitation; Spinal Cord

Ablation of the inferior olive prevents H-reflex down-conditioning in rats. - Xiang Yang Chen; Wang, Yu; Yi Chen; Chen, Lu; Jonathan Wolpaw (Journal of neurophysiology, 2016)
We evaluated the role of the inferior olive (IO) in acquisition of the spinal cord plasticity that underlies H-reflex down-conditioning, a simple motor skill. The IO was chemically ablated before a 50-day exposure to an operant conditioning protocol that rewarded a smaller soleus H-reflex. In normal rats, down-conditioning succeeds (i.e., H-reflex size decreases at least 20%) in 80% of animals. Down-conditioning failed in every IO-ablated rat (P< 0.001 vs. normal rats). IO ablation itself had no long-term effect on H-reflex size. These results indicate that the IO is essential for acquisition of a down-conditioned H-reflex. With previous data, they support the hypothesis that IO and cortical inputs to cerebellum enable the cerebellum to guide sensorimotor cortex plasticity that produces and maintains the spinal cord plasticity that underlies the down-conditioned H-reflex. They help to further define H-reflex conditioning as a model for understanding motor learning and as a new approach to enhancing functional recovery after trauma or disease.
Keywords: Spinal Cord